Effects of hydrothermal treatment of cellulose nanocrystal templated TiO2 films on their photodegradation activity of methylene blue, methyl orange, and rhodamine B. Issue 2 (15th January 2023) - Yoon, Y.H.; Lee, S.Y.; Gwon, J.G.; Vijayakumar, E.; Lee, H.G.; Lee, W.H.
Abstract: Transparent mesoporous TiO2 films with enhanced photocatalytic degradation efficiency were systematically synthesized. The films were prepared using a mixed sol containing a cellulose nanocrystal (CNC) template that was spin-coated onto an ITO substrate, followed by calcination at 400 °C for 1 h. Subsequently, the fabricated films were subjected to hydrothermal treatment in a pure aqueous medium for various periods of time (1, 2, and 4 h) and at different temperatures (150 and 250 °C). The surface area and crystallite size of the prepared TiO2 film were increased and decreased from 76.7 m 2 /g and 12.78 nm (without the template) to 127.3 m 2 /g and 9.95 nm (with the template), and then to 233.4 m 2 /g and 4.43 nm (1 h and 150 °C) with hydrothermal treatment, respectively. Hydrothermal treatment plays an important role in enlarging the surface area, and decreasing the crystallite size. Furthermore, the optimized TiO2 film exhibits exceptional photodegradation activity towards organic dyes with performance nearly equal to that of the standard photocatalyst. Because of the exceptional properties of the prepared optimized TiO2 film, the adsorption of organic dyes on its surface increases, which promotes the photocatalytic degradation efficiency during light irradiation.